Single-Tone Doppler Radar System for Human Respiratory Monitoring - Rizky Ambarini; Aloysius Adya Pramudita; Erfansyah Ali; Antonius Setiawan (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Human respiration activities can be identified from the chest wall movement. In developing a non-contacting sensor for human respiration, the chest wall movement can be detected as a Doppler shift. Therefore, the Doppler radar is potential to be implemented for the non-contacting sensor previously mention. In this paper, the Single-Tone Doppler radar which operates at 10 GHz has been studied and proposed for detecting human respiration. The simulation experimental is performed for investigating the capability of the proposed method in detecting the human respiration parameter such as respiration rate and respiration amplitude. The results show that the proposed method is capable to extract the human respiration parameter.